Sophianus palawanensis sp. nov., the first Isometopine (Hemiptera, Heteroptera, Miridae) from the Philippines - Taszakowski, Artur; Kim, Junggon; Herczek, Aleksander; Jung, Sunghoon (Zootaxa, 2021)
A new species, Sophianus palawanensis sp. nov. (Hemiptera, Heteroptera, Miridae, Sophianini) is described from the Palawan Island in the Philippines. Photographs of the male habitus and genital structures, as well as detailed SEM micrographs of selected morphological structures, are presented. Trichobothrial patterns of Sophianini and their importance for the hypothesizing relationships within Isometopinae are discussed.